Penggunaan Sinbiotik Untuk Meningkatkan Pertumbuhan Ayam Pedaging Di Peternak Muara Selayar Desa Pijot Kabupaten Lombok Timur - Muhamad Ali; Djoko Kisworo; Embun Suryani (Jurnal Gema Ngabdi, 2022)
Broiler cultivation is one of the largest MSMEs in East Lombok Regency, West Nusa Tenggara Province (NTB). The group of breeders carries out maintenance on a scale between 3,500 heads and 7,500 heads per cage. The Muara Selayar farmer group is one of the broiler farmer groups located in Pijot Village, Keruak District, East Lombok Regency. The main problem faced by the Muara Selayar Farmer Group at this time is that production performance is not optimal, which is characterized by sluggish chicken growth, many dwarf chickens, poor feed conversion, high mortality rate, which results in low profits obtained and even losses. The considerable number of dwarf chickens although it varies every period incurs losses due to poor ration conversion with low selling prices. The solution offered to bridge the problem of low broiler production performance in the Muara Selayar Broiler Farm Group is the use of symbiotic as a feed mixture for broilers of the starter period. Symbiotic are a mixture of prebiotics (feed ingredients that are difficult to digest in the digestive tract but benefit the host through selective stimulation of growth or activity of one or more microbes in the gut) and probiotics (live microbes that have benefits for the host). The results of this activity show that the use of symbiotic has succeeded in increasing the body's resistance and growth of slaughter chickens and laying hens.